2016
DOI: 10.18410/jebmh/2016/1100
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Endonasal DCR With and Without Bicanalicular Silastic Tube Insertion- A Clinical Prospective Comparative Study

Abstract: BACKGROUND The surgical management of epiphora due to Primary Acquired Nasolacrimal Duct Obstruction (PANDO) is Dacryocystorhinostomy (DCR). Endonasal DCR is becoming more popular than external DCR because of many advantages like avoidance of facial scar, reduced morbidity, lesser time consumption and ease of revision surgery. The aim of the study is to find out the success rate, complications, advantages and disadvantages of endoscopic DCR with and without silastic tube insertion. MATERIALS AND METHODS We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Mjarkesh [14] found that canalicular intubation or non-intubation gave similar results. Some authors have found an improvement in the result with the use of a silicone tube [15] [16] [17]. External dacryocystorhinostomy is simple, reproducible, and effective technique with a success rate most often greater than 80% [1] [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mjarkesh [14] found that canalicular intubation or non-intubation gave similar results. Some authors have found an improvement in the result with the use of a silicone tube [15] [16] [17]. External dacryocystorhinostomy is simple, reproducible, and effective technique with a success rate most often greater than 80% [1] [20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years endonasal and laser dacryocystorhinostomies have become very popular [16] [17]. Their advantages are numerous, as the absence of skin scars.…”
Section: Discussionmentioning
confidence: 99%